2009
DOI: 10.1111/j.1399-0004.2009.01214.x
|View full text |Cite
|
Sign up to set email alerts
|

An integrated strategy for the diagnosis of neuronal ceroid lipofuscinosis types 1 (CLN1) and 2 (CLN2) in eleven Latin American patients

Abstract: The neuronal ceroid lipofuscinoses (NCLs) are a family of progressive neurodegenerative diseases that are characterized by the cellular accumulation of ceroid lipofuscin‐like bodies. NCL type 1 (CLN1) and type 2 (CLN2) are caused by deficiencies of the lysosomal enzymes palmitoyl‐protein thioesterase 1 (PPT‐1) and tripeptidyl peptidase 1 (TPP‐1), respectively. In this study, 118 Latin American patients were examined for NCL using an integrated multidisciplinary program. This revealed two patients affected by C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 22 publications
6
43
1
1
Order By: Relevance
“…With the exception of PPT1 and TPP1 [4,32], the molecular data of this paper reflect new published results for the other genotypes. Additional data on DNA variants throughout the world are compiled at https://www.ucl.ac.uk/ncl/mutation.shtml.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 79%
See 2 more Smart Citations
“…With the exception of PPT1 and TPP1 [4,32], the molecular data of this paper reflect new published results for the other genotypes. Additional data on DNA variants throughout the world are compiled at https://www.ucl.ac.uk/ncl/mutation.shtml.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 79%
“…Transmission electron microscopy (EM) confirmed a presumed NCL disease when typical lipofuscin bodies were seen in skin biopsies: granular osmiophilic deposits (GRODs) in CLN1, curvilinear bodies (CL) in CLN2, and fingerprint profiles (FP) in CLN3 [4,6,32]. Variant morphologies were observed in the remaining genotypes.…”
Section: Electron Microscopymentioning
confidence: 70%
See 1 more Smart Citation
“…Epilepsy appears later, becoming rapidly intractable and accompanied with cognitive loss, myoclonic jerks and retinopathy. Patient autonomy is completely lost within the age of 6-8 and death occurs within adolescence period (Zhong et al, 2000;Steinfeld et al, 2002;Kohan et al, 2009). Two major distinct phenotypes have been described for classical juvenile phenotype of NCL3 (Batten disease), according to the patient's genotype: a. patients carrying the 1-kb deletion in homozygous, (firstly described in Finland and Northern Europe), and b. patients carrying a compound of 1-kb deletion with other mutations (Munroe et.…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…It is now recognized that mutations in all genes are distributed across many countries, albeit with higher incidence in some ethnic groups due to founder effects. Among the many recognized variants of NCL human forms (recent reviews in [3,6,11]), eight causal genes have been identified: CLN10/CTSD [12][13][14], CLN1/PPT1 [3,6,[15][16][17][18], CLN2/TPP1 [6,[18][19][20][21], CLN3 [22][23][24][25], CLN5 [26][27][28][29][30], CLN6 [31][32][33][34], CLN7/ MFSD8 [35][36][37][38][39], CLN8 [40][41][42]. The genes CLCN6 [43], and CLCN7 [44], and possibly SGSH [45], may also contribute to rare forms of NCL.…”
Section: Introductionmentioning
confidence: 99%